تأثير العولمة الثقافية في القيم الاجتماعية للشباب الجامعي دراسة ميدانية في جامعة دمشق (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تعرف درجات تأثير العولمة الثقافية  في القيم الاجتماعية للشباب الجامعي وذلك من خلال الإجابة عن الأسئلة التالية : 1-  ما درجات تعامل الشباب مع وسائط العولمة الثقافية ( الإنترنت ، والقنوات الفضائية) من حيث الوقت والبرامج التي يشاهدونها على القنوات الفضائية، والموضوعات التي يتصفحونها على الانترنت؟ 2-  هل يوجد اختلاف بين إجابات طلبة جامعة دمشق فيما يتعلق بتحديدهم لدرجات تأثير العولمة الثقافية في القيم الاجتماعية تعزى لمتغير الجنس أو التخصص الدراسي؟. اعتمد البحث المنهج الوصفي التحليلي باستخدام استبانة محكمة، وزعت على عينة من الشباب الجامعي قوامها (425) طالباً وطالبةً. وتوصل البحث إلى النتائج التالية: 1-  تراوح عدد الساعات التي يقضيها الشباب الجامعي في جامعة دمشق في مشاهدة برامج القنوات الفضائية بين (2-4) ساعات يومياً، واحتلت البرامج الدرامية وبرامج الأغاني والأفلام العربية والأجنبية المراتب الأولى والثانية والثالثة على التوالي، كما احتلت موضوعات الدراسات والبحوث والثقافة العلمية والدردشة المراتب الأولى والثانية والثالثة من حيث درجات تصفح الإنترنت واستخدامه من قبل أفراد العينة. 2-  توجد فروق بين متوسطات إجابات طلبة جامعة دمشق المتعلقة بتحديدهم لدرجة تأثير العولمة الثقافية في القيم الاجتماعية تعزى لمتغير الجنس، وتبين أن الفروق لصالح الذكور، ولم توجد فروق بين متوسطات إجابات طلبة جامعة دمشق المتعلقة بتحديدهم لدرجة تأثير العولمة الثقافية بالنسبة للقيم الاجتماعية بشكل عام والقيم الاجتماعية الفرعية تعزى لمتغير التخصص الدراسي. The research aims to explore the degree of cultural globalization effect in the social values for University youths through replying to these questions: -  To what extent do university youths deal with cultural globalization (internet, satellite channels) in respect to the number of hours, quality of programs and subjects which they are interested in following? The research used the descriptive analytical approach. The tool was a questionnaire that was given to (425) University youths, male and female. The results showed that the number of hours spent by the Damascus University Students – the individuals of examined specimen - in watching the TV satellite channels wavered between (2-4) hours daily; dramatic programs, Arab and foreign films and programs of songs respectively occupied the first, second and third ranks, and (71,74%) of the individuals of the examined specimen pointed out that they use the internet against (28,26%) not using it; scientific and cultural subjects occupied the first, second and third ranks with regard to the grades of internet browsing and usage by the individuals of the examined specimen. -  There are statistic differences functioning in the average of answers given by Damascus University Students relating to their definition of the effect degree of cultural globalization attributed to variable gender in the social values. The differences in these two groups fell in favor of the males and there are not statistic differences functioning in the average of answers given by Damascus University Students relating to their definition of the effect degree of cultural globalization attributed to variable academic major with regard to the social values in general.